Agora SA - Nagy, Andrea, (SAGE knowledge. Cases., 2016)
When Adam Michnik and Helena Luczywo were toiling in Poland's underground publishing world, little did they know that within a few years they would be heading up a multimedia conglomerate. During the 1970s and 80s writers in Poland were persecuted, and Michnik and Luczywo were an active part of the illegal samizdat publishing culture. But in spring 1989 everything changed. In April the Solidarity trade union was officially recognized, and in May Michnik and Luczywo began publishing Gazeta Wyborcza, the first legally independent newspaper in the Soviet communist world. Not long afterward the communist superstructure collapsed, and a new Poland was born. This case study discusses this topic.